THE GUAM PHENOMENON: ITS EXPERIENCE AS A REGIONAL COOPERATION STRUCTURE AND ITS PROSPECTS AS AN INTERNATIONAL ORGANIZATION - TOLSTOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2008)
The appearance of the GUAM (Georgia, Ukraine, Azerbaijan, and Moldova) cooperation group in the second half of the 1990s was motivated by the need to create a consultative mechanism within the framework of European international organizations in order to coordinate the positions of the member states and form regional cooperation structures. At the same time, definition of the role and clarification of the functions of GUAM at all stages of cooperation among the interested sides and development of this structure was in no way simple and unequivocal due to the changes in the transnational system and the special features of the processes occurring in the post-Soviet expanse. These circumstances demand a more in-depth assessment of the special roles played by the member states and of the regional processes that have been going on during the last 15 years.The profound political differences among the post-Soviet states in foreign policy, security, and military partnership designated after the collapse of the U.S.S.R. as early as the first half of 1992 can be regarded as the trigger that launched the formation of GUAM as a separate structural component. After refusing to sign the Collective Security Treaty at the CIS Tashkent summit on, 1992, including Ukraine, Moldova, Belarus, Azerbaijan, and Turkmenistan, voiced their objection to Russia’s dominating status in the former Soviet expanse and proclaimed their own foreign policy in the European and Euro-Atlantic context.As early as 1992-1993, political observers led everyone to believe that Kiev could become an alternative center of consolidation within the CIS. This development of events was considered a premise for the possible breakdown of the CIS into two zones, one of which would be more subject to Western influence, while the other would retain its primary orientation toward Moscow.The CIS European countries took a long time to adapt to the reality of post-bipolar Europe, and it was not an easy process. Their cooperation potential on an interstate basis, which was envisaged in the CIS founding documents, was poorly tapped. During the transition to capitalism, each of the post-Soviet states strove to set and resolve their domestic development and foreign policy tasks independently, without interacting with the other post-Soviet states. Most of the Central Asian countries and Armenia still hoped to preserve alliance relations with Russia, which was reinforced by the need to guarantee security. In contrast, the political elites of Ukraine, Moldova, Azerbaijan, and Georgia looked for ways to strengthen their independence in their relations with Moscow, rejecting participation in proto-coalition military-political structures, such as the Headquarters for Coordinating Military Cooperation among the CIS Member States (it was in effect from 24 September, 1993 to 1 January, 2006) and the Joint Command Headquarters of CIS Collective Peace-keeping Forces. The question of territorial integrity remained a constant bone of contention for the governments of Moldova, Georgia, and Azerbaijan. In so doing, Russia’s position was regarded as a serious obstacle to restoring these countries’ control over the autonomies declaring independence. Ukraine viewed the events of 1992-1994 relating to the status of the Black Sea Fleet and the separatist moods in the Crimea as confirmation of Russia’s imperial ambitions.